WY-14643 and 9-cis-retinoic acid induce IRS-2/PI 3-kinase signalling pathway and increase glucose transport in human skeletal muscle cells: differential effect in myotubes from healthy subjects and Type 2 diabetic patients - Bouzakri, K.; Roques, M.; Debard, C.; Berbe, V.; Rieusset, J.; Laville, M.; Vidal, H. (Diabetologia, 2004)
To determine the effects of peroxisome proliferator-activated receptor alpha (PPARalpha) and retinoid X receptor (RXR) agonists on insulin action, we investigated the effects of Wy-14643 and 9- cis-retinoic acid (9- cis-RA) on insulin signalling and glucose uptake in human myotubes. Primary cultures of differentiated human skeletal muscle cells, established from healthy subjects and Type 2 diabetic patients, were used to study the effects of Wy-14643 and 9- cis-RA on the expression and activity of proteins involved in the insulin signalling cascade. Glucose transport was assessed by measuring the rate of [(3)H]2-deoxyglucose uptake. Wy-14643 and 9- cis-RA increased IRS-2 and p85alpha phosphatidylinositol 3-kinase (PI 3-kinase) mRNA and protein expression in myotubes from non-diabetic and Type 2 diabetic subjects. This resulted in increased insulin stimulation of protein kinase B phosphorylation and increased glucose uptake in cells from control subjects. Myotubes from diabetic patients displayed marked alterations in the stimulation by insulin of the IRS-1/PI 3-kinase pathway. These alterations were associated with blunted stimulation of glucose transport. Treatment with Wy-14643 and 9- cis-RA did not restore these defects but increased the basal rate of glucose uptake. These results demonstrate that PPARalpha and RXR agonists can directly affect insulin signalling in human muscle cells. They also indicate that an increase in the IRS-2/PI 3-kinase pathway does not overcome the impaired stimulation of the IRS-1-dependent pathway and does not restore insulin-stimulated glucose uptake in myotubes from Type 2 diabetic patients.